Commercial golf glove effects on golf performance and forearm muscle activity - Sorbie, G. G.; Darroch, P.; Grace, F. M.; Gu, Y.; Baker, J. S.; Ugbolue, U. C. (Research in Sports Medicine, 2017)
The study aimed to determine whether or not commercial golf gloves influence performance variables and forearm muscle activity during golf play. Fifteen golfers participated in the laboratory based study, each performing 8 golf swings with a Driver and 7-iron whilst wearing a glove and 8 without wearing the glove. Club head speed, ball speed and absolute carry distance performance variables were calculated. Surface electromyography was recorded from the flexor digitorum superficialis and extensor carpi radialis brevis on both forearm muscles. Club head speed, ball speed and absolute carry distance was significantly higher when using the Driver with the glove in comparison to the Driver without the glove (p < 0.05). No significant differences were evident when using the 7-iron and no significant differences were displayed in muscle activity in either of the conditions. Findings from this study suggest that driving performance is improved when wearing a glove.